The limits of neuroscience in business : before investing in products or services that claim to provide business insights based on brain research, managers should understand several key issues with neuroscientific solutions - Horvath, Jared Cooney (MIT Sloan Management Review, 2022)
Products and services that claim to provide business insights based on brain research are proliferating, but some of these applications may be of limited value. This article educates managers on some underlying issues with translating neuroscience findings into information that's useful for business.